(A reading in the problems of the Islamic conquest of Barqa 22 AH / 642 AD "Saleh Loata" as a model) (Journal of Humanitarian and Applied Sciences, 2023)
Extrapolating a number of historical narratives of the Arab-Islamic conquest of Cyrenaica in the first century AH / seventh century AD, makes us stand at some circumstances that may provoke wonder or disgust, and that may not conform to the approach of wise law, which is to respect human rights in dealing with the other. Therefore, the choice of the title of the research topic was: (Reading in the problems of the Islamic conquest of Cyrenaica 22 AH / 642 AD "Reform of Loytah" as a model), to find out the essence of this topic and its details according to the agreed historical research method.The research includes important and vital problems in the Islamic history of Libya, the most important of which are:* Stand up for the rapid advance of the Arab Islamic Army led by "Amr bin Al-Aas" towards Cyreqa immediately after the opening of Alexandria?* Peace of Luate, what are the origins of this tribe? And what is its position among other Berber tribes to lead the historical event by reconciling with Amr bin Al-Aas? And did Muslims know the Berbers before this event?* The main problem here in one of the conditions of the peace is the sale of the Al-Walwali to their children in case they are unable to pay the jizya to Muslims! And the question raised here: How is the justice of the religion of Islam and the sale of fathers to children and their bargaining in the dearest and most precious thing they have?!! How do we explain that and the principles of Islam came to lift the injustice of the people?!!Can we doubt the narratives contained in many mothers of historical books - which may be turbulent or repetitive or both! - or whether the historical consensus on the event makes us confirm its occurrence under any justification!!* The conclusion of the study was followed by a set of important recommendations that serve the Libyan library.